An emission-free controlled potassium pyrosulfate roasting-assisted leaching process for selective lithium recycling from spent Li-ion batteries. (November 2022) - Liu, Chunli; Ji, Haiyan; Liu, Jiayin; Liu, Pengfei; Zeng, Guisheng; Luo, Xubiao; Guan, Qian; Mi, Xue; Li, Yingpeng; Zhang, Jiefei; Tong, Yongfen; Wang, Zhongbing; et al.
Graphical abstract: Highlights: We develop a clean method of recovering valuable metals from spent LiCoO2 batteries. Li is selectively extracted by potassium pyrosulfate roasting and water leaching. The method achieves a high Li recovery rate and no SOx emissions. The reaction mechanisms governing metal transformation are elucidated. Li2 CO3 (>99.5 % pure) and Co3 O4 (>99.5 % pure) are obtained as valuable products. Abstract: Recycling critical metals from spent Li-ion batteries (LIBs) is important for the overall sustainability of future batteries. This study reports an improved sulfation roasting technology to efficiently recycle Li and Co from spent LiCoO2 LIBs using potassium pyrosulfate as sulfurizing reagent. By sulfation roasting, LiCoO2 was converted into water-soluble lithium potassium sulfate and water-insoluble cobalt oxide. Under optimal conditions, 98.51% Li was leached in water, with a selectivity of 99.86%. More importantly, sulfur can be recirculated thoroughly, and the sulfur atomic efficiency can be significantly enhanced by controlling the amount of potassium pyrosulfate. Li ions from the water leaching process were recovered by chemical precipitation. Furthermore, application of this technology to other spent LIBs, such as LiMn2 O4 and LiNi0.5 Co0.2 Mn0.3 O2, verified its effectiveness for selective recovery Li. These findings can provide some inspiration for high efficiency and environmentally friendly recovery metal from spent LIBs.